Directors’ perceptions of parent involvement in the Early Head Start and Sure Start early intervention programs: a cross-Atlantic study - Ross, KB (2010)
This research is a cross-Atlantic study of Sure Start and Early Head Start program directors' perceptions of parent involvement in their early intervention programs, with a focus on the provision and take-up of parenting and employability-focused services. The review of the literature, which informed the survey design and the later data chapters, focuses on poverty and parenting, working parents, welfare reform, and early intervention programs, including early childhood education and care policies in England and the United States. Data was collected via an online survey, administered to all those individuals directing either a Sure Start Local Programme (including those that had been designated as Children's Centres) in England or an Early Head Start program in the USA. There was a 40.3% response rate (231 English and 236 American directors, resulting in a total of 467 respondents). The survey questioned directors on their background, and also sought their views of the area in which their program operated, characteristics of their programs and their perceptions of the families accessing the parent-focused services offered by their early intervention program. The resulting data was used to address the primary theme of parenting and employability, drawing associations between reported parent involvement and directors' perceptions of area, program and family characteristics. The findings also led to the establishment of secondary themes: the targeting and catchment area approach to service provision, engaging disadvantaged families, relationships with partner agencies, issues of funding and resources, particularly for staff, and the expansion of Children's Centres. A summary report was sent to all participating directors. It is hoped that this research has benefited program directors, providing insights into the local-level experiences had by their colleagues both within their own country and across the Atlantic, particularly with respect to parent involvement in early intervention programs.